HISTOPATOLOGI HATI IKAN PATIN YANG DIBERI PAKAN MENGANDUNG TEPUNG KUNYIT - Sri Wahyuni; Morina Riauwaty; Windarti Windarti (Universitas Sriwijaya, 2020)
This research was conducted from February to May 2019. The purpose of this study was to determine the network structure of striped catfish fed with turmeric flour before and after being tested with Aeromonas hydrophila. Sampling of histopathological preparations was carried out 2 times, namely at the beginning of maintenance, 30 days of maintenance and 14 days after the challenge test. The observed organ was the liver. The results of histological observations of catfish liver for 30 days of maintenance and fed with turmeric flour were still good. The structure of liver tissue after being challenged in treatment P1, P2 and P3 suffered damage such as hypertrophy, vacuole degeneration and necrosis. The best dose of adding turmeric flour to feed is 0.7 g / kg (P2) with the least damage.Key words: Striped fish, histopathology, liver, necrosis, turmeric flour